2014
DOI: 10.1111/eci.12247
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 and clustering of metabolic syndrome components in pediatrics

Abstract: Our data indicate that changes in circulating IL-10 concentrations are marker of metabolic risk in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…IL-6 and TNF-α are significantly increased in patients with metabolic syndrome 47–49. Previous study showed that the circulating anti-inflammatory cytokine IL-10 concentration is lower in obese children, negatively correlated with percentage of body fat, and can serve as a marker for metabolic risk in children 50. In this study, CRP correlates independently with the cytokines that are known to be associated with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 55%
“…IL-6 and TNF-α are significantly increased in patients with metabolic syndrome 47–49. Previous study showed that the circulating anti-inflammatory cytokine IL-10 concentration is lower in obese children, negatively correlated with percentage of body fat, and can serve as a marker for metabolic risk in children 50. In this study, CRP correlates independently with the cytokines that are known to be associated with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 55%
“…Interleukin-10 and metabolic syndrome IL-10 is a potent anti-inflammatory cytokine that modulates the immune response in order to prevent excessive activation and auto-damage [36]. Based on its properties, IL-10 plays important roles in modulating insulin resistance and atherosclerotic development and, in a cross-sectional study conducted on children and young adolescents, it has been found that plasmatic IL-10 levels were lower in overweight/obese children, and they concluded that IL-10 could be a marker of metabolic risk [37]. On the contrary, Esposito et al found that IL-10 levels were lower in obese compared with normal weight women, but were lower in both groups that had MetS criteria [38].…”
Section: Interleukin-10mentioning
confidence: 99%
“…Paraoxonase-1 (PON-1) was inversely correlated with the presence of MetS, more precisely with central obesity, hypertriglyceridemia, and hypertension [32][33][34][35]. Interleukin-10 (IL-10) is an anti-inflammatory cytokine, and decreased levels of IL-10 are associated with insulin resistance and the presence of MetS [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Interleukin-10 (IL-10), a cytokine, contains variable antiinflammatory properties and controls insulin sensitivity and cholesterol uptake and efflux in macrophages. [41][42][43] IL-10 is produced from many organs, including spleen. It acts via the IL-10 receptor to activate the JAK/STAT pathway and exerts immunosuppressive effects by blocking IκK activity or by inducing tyrosine phosphorylation of STAT-3.…”
Section: Discussionmentioning
confidence: 99%